Bright persistent luminescence from Cu+ activated Al2O3–CaO photochromic glasses. Issue 7 (1st April 2023) - Wang, Panting; Du, Ying; Tao, Yiting; Wu, Ting; Chen, Danping
Abstract: Using the photochromic glass to prepare glass with long persistence lifetime is a new strategy to develop persistent luminescent (PersL) glass. A novel Cu  +  doped Al2 O3 –CaO PersL glasses were found according to the strategy. The Cu  +  doped Al2 O3 –CaO glasses were papered in reducing conditions, which not only showed double luminescence characteristic of Cu + at 457 nm and 480 nm after irradiated by ultraviolet light source or sunlight, but also emitted bright and lasting green light after cutting off the excitation source. The persistence lifetime of the glass is positively correlated with the content of Al2 O3, and the longest lifetime can reach 10.5 h. The spectral properties of the glasses were analyzed by absorption spectrum, fluorescence spectrum, thermoluminescence spectrum and EPR. Based on these results and the photochromic properties of the glass, the PersL is explained by a model of "storage" and "release" electrons generated by electronic defects in the glasses prepared in reducing atmosphere.